Study of Lampung Local Wisdom for the Development of Science Learning Materials in the Context of Environmental Conservation - Aini, Via; Hidayat, Topik; Kusnadi, Kusnadi; Nahadi, Nahadi; Anwar, Sjaeful (Universitas Lampung, 2023)
Local wisdom is built from the existence of social values that are upheld in the social structure of the community taught from generation to generation. Some of them can be used in implementing science learning commonly called ethnoscience. However, not all local wisdom can be used as science learning materials. This study aims to examine the local wisdom of Lampung that can be used for the development of science learning materials that are in accordance with the nature of science, which must have rational, empirical values, and can be verified or proven scientifically. This research is a literature study by looking for relevant research references. The research procedure is carried out in stages, namely collecting library materials, reading, recording, studying, collecting concepts or manuscripts and then elaborating from the data collected. The results obtained are 5 local wisdom that can be elaborated with science learning in the context of environmental conservation, namely Nyalau, repong damar, bubu, ngelahang and the ban on mangrove clearance.